2011
DOI: 10.1099/jmm.0.034876-0
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Mycobacterium tuberculosis strains from foreign-born patients in Korea

Abstract: Information on drug resistance and transmission patterns of tuberculosis (TB) in foreign-born patients is lacking in Asia where immigration is increasing. We examined the drug-resistance profiles of 288 Mycobacterium tuberculosis isolates from foreign-born patients in South Korea, and assessed for potential transmission in the host country by analysing their IS6110 genotypes, as well as those of 4780 strains from native Korean TB patients. The prevalence of multidrugresistant (MDR) TB was 9.7 % and 42 % among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Red=Beijing strain. 103,104,[105][106][107][108][109][110][111][112] Green=LAM9 strain. 113 Light blue=Haarlem1 strain.…”
Section: Figurementioning
confidence: 99%
“…Red=Beijing strain. 103,104,[105][106][107][108][109][110][111][112] Green=LAM9 strain. 113 Light blue=Haarlem1 strain.…”
Section: Figurementioning
confidence: 99%
“…The most common countries of origin are China, Mongolia, Pakistan, Philippines, Vietnam, and North Korea ( 34 ). The proportion of TB patients of foreign nationality has been increasing in recent years, from 0.3% in 2001 to 3.8% in 2013 ( 17 ).…”
Section: Part II Reasons For the High Burden Of Tb In South Koreamentioning
confidence: 99%
“…Considering the similarities of the MTB_2 strain isolated from a male Korean-Chinese (Chosun race) individual who emigrated from Yanbian Province, China, with the native Korean K1 strains (Nos. 1 and 2), he may have been infected with a strain from native Koreans after immigration, as Jeon et al 6 reported, because the Korean K1 strains have been reported as the most widely distributed characteristic strains in South Korea 5 . Otherwise, another plausible explanation is that the strains from Yanbian Province, where Chosun race live because of the geographical proximity to the Korean Peninsula, may have the same lineage as the native Korean K strains.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is essential to determine the molecular epidemiology of Mycobacterium tuberculosis isolates and identify the transmission dynamics in the Korean-Chinese population to define a strategy for immigration TB screening. A clustering of M. tuberculosis strains from native Koreans (K family) was reported 5 , and it was different from that of foreign-born patients according to restriction fragment length polymorphism profile analyses 6 .…”
Section: Introductionmentioning
confidence: 99%